Direct Oral Anticoagulant Use and Risk of Diverticular Hemorrhage: A Systematic Review of the Literature - MacKenzie Turpin; Peter Gregory (Canadian Journal of Gastroenterology and Hepatology)
Background. Anticoagulants carry a significant risk of gastrointestinal bleeding. With the increase in use and availability of direct oral anticoagulants (“DOACs”) more data are available regarding the risks of these medications. With diverticular bleeds being common, and hospitalization associated with gastrointestinal bleed increasing 30-day mortality, it is paramount to better understand the potential risks of using DOACs in this population. Methods. A systematic review of the literature was undertaken, using the databases PubMed, EMBASE, Cochrane Library, and CINAHL. Two reviewers independently searched the literature, and initial screening was performed through title and abstract reading. Search terms included “direct” AND “anticoagulant” AND “diverticular bleed” OR “diverticular hemorrhage”. The references of the selected studies were manually reviewed for any further relevant articles. Results. Literature search across the databases garnered 182 articles—157 unique abstracts after duplicate removal. Based on inclusion and exclusion criteria, 6 studies were deemed relevant. The selected studies’ reference lists yielded no further relevant articles. Discussion. Across the 6 studies, the incidence of diverticular bleeding in patients using DOACs was extremely low. Of 23,990 patients taking DOACs identified from two separate institutions, only 60 were found to have diverticular hemorrhage. Similarly, among 15,056 patients with diverticular hemorrhage, only 246 (1.6%) among them were taking DOACs. Generally, the studies found no increased diverticular bleeding rate between patients taking DOACs and those who were taking other anticoagulants, such as warfarin, or the general population. The studies also did not find an increased risk of rebleeding with DOAC continuation. Conclusion. The evidence suggests the risk of diverticular bleed among DOAC users is equivocal to those not taking DOACs, and the overall incidence of diverticular bleed in the DOAC population is low. As it stands, the risk of thrombotic events from not starting DOACs apparently outweighs the risk of diverticular bleed.